Hidden hope : how a toy and a hero saved lives during the Holocaust - Boxer, Elisa (Abrams Books for Young Readers, 2023)
"During World War II, families all across Europe huddled together in basements, attics, and closets as Nazi soldiers rounded up anyone Jewish. The Star of David, a symbol of faith and pride, became a tool of hate when the Nazis forced Jewish people to carry papers stamped with that star, so that it was clear who to capture. But many brave souls dared to help them. Jewish teenager Jacqueline Gauthier, a member of the French Resistance who had to conceal her identity, was one who risked her life in secret workshops, forging papers with new names and without stars in order to help others escape. But how to get these life-saving papers to families in hiding? An ordinary wooden toy duck held the answer, a hidden compartment: hope in a hollow. Written by award-winning journalist Elisa Boxer and movingly illustrated by the acclaimed Amy June Bates, Hope in a Hollow celebrates the triumph of freedom and the human spirit, a story of everyday heroism, resilience, and finding hope in unexpected places"--